Analysis of Decision Number 172 K/Pdt.Sus-Hki/2024 in the IPR Dispute Between Jollibee Foods Corporation and PT Tatalogam Lestari - Tuasikal, Naisyirah Ramadhani (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The Supreme Court of the Republic of Indonesia in cassation case Number 172 K/Pdt.Sus-HKI/2024 provided in-depth legal considerations regarding the trademark dispute between JOLLIBEE FOODS CORPORATION and PT Tatalogam Lestari. This decision confirms that the "JOLIBI" mark belonging to PT Tatalogam Lestari was registered in bad faith and is substantially similar to the "JOLLIBEE" mark belonging to JOLLIBEE FOODS CORPORATION. The Supreme Court assessed that the similarities in the form, placement, writing and sound of the two marks could cause confusion among consumers. In addition, the Supreme Court considered that PT Tatalogam Lestari should have known about the existence of the "JOLLIBEE" mark which was registered and widely used, so that the registration of the "JOLIBI" mark was deemed to have been carried out in bad faith. The evidence presented by JOLLIBEE FOODS CORPORATION, including promotion through social media and search engines as well as evidence of consistent use, succeeded in convincing the Supreme Court that the "JOLLIBEE" mark is a well-known mark that deserves stronger legal protection. This decision emphasizes the importance of protecting well-known brands and preventing trademark registration actions in bad faith that can harm the original brand owner and mislead consumers.